Pharmacological rescue of mitochondrial and neuronal defects in SPG7 hereditary spastic paraplegia patient neurons using high throughput assays - Wali, Gautam; Li, Yan; Liyanage, Erandhi; Kumar, Kishore R.; Day, Margot L.; Sue, Carolyn M. (Frontiers in Neuroscience, 2023)
SPG7 is the most common form of autosomal recessive hereditary spastic paraplegia (HSP). There is a lack of HSP-SPG7 human neuronal models to understand the disease mechanism and identify new drug treatments. We generated a human neuronal model of HSP-SPG7 using induced pluripotent stem (iPS) cell technology. We first generated iPS cells from three HSP-SPG7 patients carrying different disease-causing variants and three healthy controls. The iPS cells were differentiated to form neural progenitor cells (NPCs) and then from NPCs to mature cortical neurons. Mitochondrial and neuronal defects were measured using a high throughout imaging and analysis-based assay in live cells. Our results show that compared to control NPCs, patient NPCs had aberrant mitochondrial morphology with increased mitochondrial size and reduced membrane potential. Patient NPCs develop to form mature cortical neurons with amplified mitochondrial morphology and functional defects along with defects in neuron morphology − reduced neurite complexity and length, reduced synaptic gene, protein expression and activity, reduced viability and increased axonal degeneration. Treatment of patient neurons with Bz-423, a mitochondria permeability pore regulator, restored the mitochondrial and neurite morphological defects and mitochondrial membrane potential back to control neuron levels and rescued the low viability and increased degeneration in patient neurons. This study establishes a direct link between mitochondrial and neuronal defects in HSP-SPG7 patient neurons. We present a strategy for testing mitochondrial targeting drugs to rescue neuronal defects in HSP-SPG7 patient neurons.